The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.2214/ajr.12.9563
|View full text |Cite
|
Sign up to set email alerts
|

Added Value of Diffusion-Weighted Acquisitions in MRI of the Abdomen and Pelvis

Abstract: OBJECTIVE The purpose of this article is to review abdominopelvic applications of diffusion-weighted imaging (DWI), discuss advantages and limitations of DWI, and illustrate these with examples. CONCLUSION High-quality abdominopelvic DWI can be performed routinely on current MRI systems and may offer added value in image interpretation. Particularly in unenhanced MRI examinations, DWI may provide an alternative source of image contrast and improved conspicuity to identify and potentially characterize patholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
3

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 39 publications
0
31
0
3
Order By: Relevance
“…The diagnostic rate of tumors with MDCT is higher with a sensitivity of 69 to 84% and specificity of 59 to 83% [15,16].…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The diagnostic rate of tumors with MDCT is higher with a sensitivity of 69 to 84% and specificity of 59 to 83% [15,16].…”
Section: Resultsmentioning
confidence: 97%
“…On the other hand, although conventional MRI sequences may be helpful to detect a pathological lesion, they cannot adequately differentiate between malignant and benign lesions [16,17].…”
Section: Resultsmentioning
confidence: 99%
“…As a result, when compared to benign tumors, in malignant tumors DW-MRI also provides a bright signal reflecting the restricted diffusion, and low ADC values in ADC mapping. However, signal intensities of the blood clot cause various signal intensities on the DW-MRI, with T2 brightness or T2 dimming effects, depending on the age of bleeding (22). Most studies on hematoma ADC measurements have shown results with a predisposition for low values (23,24).…”
Section: Dw-mri Was First Used In Cranial Imaging In the Diagnosismentioning
confidence: 99%
“…Si bien estos hallazgos son habituales de observar, aún no se establece una adecuada especificidad diagnóstica con este método de estudio, requiriéndose mayor investigación en esta área. Sin embargo, estas secuencias pueden servir de ayuda, cuando el uso de gadolinio está contraindicado o cuando las otras adquisiciones del estudio son subóptimas 21,22 logía tuberculosa de estas alteraciones se describen algunos signos relativamente específicos para su diagnóstico. En el caso de la espondilodiscitis estos signos corresponden a una relativa preservación de la amplitud del espacio discal, con una afectación multisegmentaria (generalmente del segmento torá-cico), y un compromiso vertebral predominantemente anterior (por diseminación contigua subligamentaria entre cuerpos vecinos.…”
Section: Hallazgos De Imagenunclassified